The theatrical game : A comparative study of selected English and Arabic plays - Heidi Mohamed Bayoume; Amal Aly Mazhar (Cairo : Heidi Mohamed Bayoume, 2010)
This study deals with the use of game in selected Arabic and English drama in order to shed light on the game, its different manifestations, its role in relation to the overall structure of the play, its different elements (players and disguise), and its role in delivering the different social, religious, philosophical and political messages of the playwright
Thesis (M.A.) - Cairo University - Faculty of Arts - Department of English
Issued also as CD
Keywords: Kinetic games; Theatrical games; Verbal games